2013
DOI: 10.1002/jsfa.6377
|View full text |Cite
|
Sign up to set email alerts
|

Grape brandy production, composition and sensory evaluation

Abstract: Grape brandy is a spirit drink produced by wine distillation and is matured in wooden casks. According to legislation, it can be characterised by the geographical area where the grapes were produced, the grape variety used and the selected distillation and ageing techniques. Distillation increases ethanol concentration and aromatic constituents which are already present in grapes or are developed during fermentation and distillation. During maturation in wooden casks, compounds that contribute to the aroma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 62 publications
(60 reference statements)
7
64
1
1
Order By: Relevance
“…The percent of alcohol by volume is now the harmonized measurement for alcohol strength (8). The accurate and rapid determination of ethanol in alcoholic beverages is very important for safety and economic reasons (8, 10). Some studies have shown that the unrecorded alcoholic beverages have higher ethanol levels than those that are commercially available (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percent of alcohol by volume is now the harmonized measurement for alcohol strength (8). The accurate and rapid determination of ethanol in alcoholic beverages is very important for safety and economic reasons (8, 10). Some studies have shown that the unrecorded alcoholic beverages have higher ethanol levels than those that are commercially available (3).…”
Section: Discussionmentioning
confidence: 99%
“…Total acidity in alcoholic beverages is initially due to the presence of volatile acids, such as acetic acid or tartaric acid, and dictates the chemical processes taking place in alcoholic beverages (10, 20). In the current research, we have studied the general composition of noncommercial alcohol samples.…”
Section: Discussionmentioning
confidence: 99%
“…Spirits produced from pot stills are normally perceived to be more aromatic than spirits elaborated from continuous stills . Generally, spirits are aging into oak barrels where some phenolics and volatile compounds are extracted . Aging on oak barrels accelerates acid‐catalyzed reactions like ester hydrolysis and formation compared to those aged in glass .…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 99%
“…Of the monocarboxylic acid esters, the most important in brandy are those based on ethanol and saturated carboxylic acids, such as hexanoic (caproic), octanoic (caprylic) and decanoic (capric) acids [25]. In our study, the ranges of ethyl hexanoate and ethyl octanoate were 132-1687 µg/L and 349-23,429 µg/L, respectively, with B having the highest concentration of both compounds.…”
Section: Five Weeks Post-disgorgingmentioning
confidence: 51%